2012
DOI: 10.1044/1092-4388(2011/11-0101)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Speaker Age on Speech Recognition and Perceived Listening Effort in Older Adults With Hearing Loss

Abstract: Purpose: Older adults exhibit difficulty understanding speech that has been experimentally degraded. Age-related changes to the speech mechanism lead to natural degradations in signal quality. We tested the hypothesis that older adults with hearing loss would exhibit declines in speech recognition when listening to the speech of older adults, compared with the speech of younger adults, and would report greater amounts of listening effort in this task.Methods: Nineteen individuals with age-related hearing loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…No significant difference in speech recognition existed when stimuli were derived from younger and older speakers. However, perceived effort was significantly higher when listening to speech from older adults, as compared with younger adults [ 24 ]. That study revealed that older listeners with hearing loss exhibited similar levels of speech understanding when listening to the speech of younger and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in speech recognition existed when stimuli were derived from younger and older speakers. However, perceived effort was significantly higher when listening to speech from older adults, as compared with younger adults [ 24 ]. That study revealed that older listeners with hearing loss exhibited similar levels of speech understanding when listening to the speech of younger and older adults.…”
Section: Discussionmentioning
confidence: 99%
“…After the final noise offset, the participants were prompted to decide whether the sentence matched the picture or not via a button press (left or right mouse button). After the comprehension task, the participants were instructed to rate how difficult it was to understand the sentence using a continuous visual analog scale ( McAuliffe et al, 2012 ). They were asked to indicate their rating by positioning a mouse on a continuous slider marked “easy” and “difficult” at the extremes.…”
Section: Methodsmentioning
confidence: 99%
“…A trained research assistant transcribed listener responses in real time. Responses were also audio-recorded, and the transcriptions were crosschecked prior to data coding and analysis (as per McAuliffe et al, 2012McAuliffe et al, , 2013. We chose this process over a standard computer-based transcription task because it enables younger listener transcriptions to be compared with older listener transcriptions (e.g., McAuliffe et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Perceptual selection and acoustic verification. As is usual in studies of this kind, a phrase selection and verification process was undertaken (e.g., Borrie et al, 2012;Liss et al, 1998Liss et al, , 2000McAuliffe, Wilding, Rickard, & O'Beirne, 2012). The intent of this process was to select phrases from each speaker that most strongly conformed to our perceptual criteria (as judged by two expert judges, the first and third authors) and subsequently to verify acoustically these perceptual impressions.…”
Section: Experimental Stimulimentioning
confidence: 99%